2021
DOI: 10.1111/ijsw.12501
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent gambling advertising awareness: A national survey

Abstract: While influence of gambling advertisements on adolescents in some jurisdictions is recognised as an important public health issue, research examining this influence is currently limited. The present study examined gambling advertising awareness among adolescents, how they perceive gambling advertisement's impact, and how gambling advertisement awareness relates to adolescent's gambling behaviour. A sample of Danish adolescents (n = 1137) aged 12-16 were surveyed using a self-administered web questionnaire. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Current findings highlight the need to further explore the impacts of online gambling advertising on young people’s gambling behaviours, particularly in the Australian context. The link between online advertising and youth gambling is concerning given the rapid expansion of gambling advertising into the digital sphere via online and social media marketing, ( Torrance et al, 2021 ) and that young people tend to have the highest use of the internet and social media ( Gainsbury et al, 2016 , Kristiansen and Severin-Nielsen, 2021 ). Young people can access gambling via betting or related apps, ( King et al, 2020 ) where online advertising may be targeted towards the types of gambling activities that the young person engages in.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current findings highlight the need to further explore the impacts of online gambling advertising on young people’s gambling behaviours, particularly in the Australian context. The link between online advertising and youth gambling is concerning given the rapid expansion of gambling advertising into the digital sphere via online and social media marketing, ( Torrance et al, 2021 ) and that young people tend to have the highest use of the internet and social media ( Gainsbury et al, 2016 , Kristiansen and Severin-Nielsen, 2021 ). Young people can access gambling via betting or related apps, ( King et al, 2020 ) where online advertising may be targeted towards the types of gambling activities that the young person engages in.…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 review found that most gambling operators did not incorporate responsible gambling messaging in their use of social media, despite this being a requirement of most advertising codes of conduct ( Gainsbury et al, 2016 ). In addition, advertising via social media may be particularly appealing to young people, because postings might not be recognised as advertising, and content can be shared and promoted by peers, including to underage users ( Kristiansen and Severin-Nielsen, 2021 , O’Loughlin and Blaszczynski, 2018 ). Restrictions on gambling advertising have been identified as a potentially cost-effective measure for reducing harms associated with gambling ( Bouguettaya et al, 2020 , Parrado-González and León-Jariego, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Advertising of loan advancers which meet the Financial Standards Authority's definition of 'High Cost Short Term (HCST)' Similar to advertisement for HFSS (and alcohol and tobacco products), associations between gambling advertisement and adverse impact, especially on young people, have been described (23,24), including on self-perceived at-risk or problematic gambling (25); mainly through triggering impulses to gamble (26). This new Advertisement Policy came into force at the end of 2021, but practically came into effect in April 2022 when the first existing advertising contracts came to an end.…”
Section: Introductionmentioning
confidence: 99%